Respuesta :
2(x-3)+3=6x-5
2x-6+3=6x-5
2x-3=6x-5
+3 +3
2x=6x-2
-6x -6x
-4x=-2
———
-4x -4x
x=1/2
2x-6+3=6x-5
2x-3=6x-5
+3 +3
2x=6x-2
-6x -6x
-4x=-2
———
-4x -4x
x=1/2
x = 0.5
What is the distributive property?
According to the distributive property, an expression in the form P (q + r) can be resolved as p (q + r) = pq + pr. This distributive law, which is represented as p(q - r) = pq - pr, also applies to subtraction. This indicates the distribution of operand A among the other two operands.
The solution to the problem
Using the distributive property to solve the problem:
2x - 2*3 + 3 = 6x -5
Transposing 2x on RHS and -5 to LHS
5-6+3 = 6x - 2x
2 = 4x
Dividing the equation by 4
x = 1/2 = 0.5
Hence the solution to the given equation using distributive property is 0.5
Learn more about the distributive property here
https://brainly.com/question/2807928
#SPJ2